Domestication of open educational resources by academics in an open distance e-learning institution of South Africa - Mncube, Lancelord Siphamandla (Department of Information Systems, 2022)
The emergence of open educational resources has gained popularity and acceptance in higher education institutions and beyond the basic education sector. This brought a persisting shift in depending on information communication technologies for tuition and research provision. Information technology artifact was not treated in isolation to user perspective. The study established how academics accept, feel, perceive, and what skills, opportunities, challenges exist to hinder the domestication. The study context had no uniform guidelines or tools and policy in place for the domestication of open educational resources. The study adopted the exploratory approach guided by the interpretivism paradigm. The study employed Domestication theory. This study conducted in an heterogenous single case study, which is the open distance e-learning (University of South Africa). That was done for an in-depth investigation by relying on multi-methods for data triangulation such as semi-structured interviews, focus group interviews, document analysis, and actual artifact analysis. The total of participants were 52. The study found that most academics played a role in the domestication of open educational resources besides the minority who were unable. The experience and prior knowledge were found to be a factor hindering the domestication process. Open distance e-learning found to relevant space for open educational resources. Such institutions play a role in the adoption and development of open educational resources and mostly rely in information technology for tuition and research. Information technology infrastructure found to be an enabler and disabler in the domestication process. This study contribution to the world of knowledge is based on the theory and practice. Eight theoretical propositions were suggested. The study further contributed by extension of domestication theory as recommended two additional phases which are non-appropriation and dis-appropriation. The current proposed Domestication theory has five phases. Lastly, the study recommended the actual guidelines for adoption and development of open educational resources. This guideline can be adopted by higher education institutions by infusing them in policy development or for general guidance in actual adoption and developments.